Elimination of Double‐Slope Nonideality in C60 Field Effect Transistors - Xingwei Zeng; Xinyi Zhao; Jianbin Xu; Qian Miao (Advanced Electronic Materials)
Abstract Double‐slope nonideality, widely observed in organic field‐effect transistors (OFETs), leads to inaccurate extraction of field‐effect mobility, hindering the evaluation of new organic semiconductors and limiting OFET applications. This study presents a solution to this issue in n‐type OFETs based on C60. Applying a pre‐scan reversed gate‐source bias (PRGSB) eliminates the double‐slope nonideality. This discovery emerges serendipitously during an experiment where the source and drain connections are accidentally swapped. On the basis of the gradual formation of the active channel as the gate voltage increases, it is proposed that the double‐slope nonideality stems from high‐density traps in the semiconductor layer near the source electrode, presumably due to defects introduced during vacuum deposition of gold contact. The application of PRGSB injects positive charges into the dielectric layer via a large source‐gate voltage. When this voltage is removed, the trapped charges act as an additional gate voltage during subsequent gate scans, filling the traps near the source and correcting the nonideality in the transfer I–V curve. These findings offer a new approach to addressing the double‐slope nonideality challenge in OFET characterization and suggest an unprecedented explanation for this phenomenon.